Decoration in the interior of mosque : a review of current literature / Norhayati Kassim, Norashikin Abdullah and Mohd. Zafrullah Haji Mohd. Taib - Kassim, Norhayati; Abdullah, Norashikin; Mohd. Taib, Mohd. Zafrullah (2012)
Mosques are decorated with either high or less decoration. The most part which decorated normally with decorative pattern especially on the kiblah wall. The decoration in the interior of mosque gives both negative and positive impacts to the mosque user. Some scholars are agreed with the ornamentation in the interior mosque through Islamic art concept and some are not based on the prophet‟s mentioned tradition. Therefore this paper will present an overview of current literatures on the discussion about the ornamentation in interior mosque. This paper will cover the function of ornamentation and decorative pattern in interior mosque as well the advantages and disadvantages of using it.